UPAYA PENGENDALIAN PENYAKIT LAYU FUSARIUM OXYSPORUM DENGAN PEMANFAATAN AGEN HAYATI CENDAWAN FMA DAN TRICHODERMA HARZIANUM - Alfizar Alfizar; Marlina Marlina; Nurul Hasanah (Jurnal Floratek, 2011)
The objectives of the research were to determine effectiveness of antagonist T. harzianum and fungi micorrhyze in suppressing growth of Fusarium oxysporum on tomato. The research used a factorial completely randomized design, consisting of sixteen combination treatments and three replications. The first factor was doses of T. harzianum, consisting of four levels, i.e. 0, 15, 30, and 45 g.polybag-1.  The second factor was doses of micorrhyze, also consisting of four levels, i.e. 0, 5, 10, and 15 g.polybag-1. Variables observe were incubation period, length of xylem discoloration and percentage of wilting plant. The data were analyzed statistically by analysis of variance. The least significant difference test (LSD) at the 0.05 level was used to see the difference between the treatments. The results showed that applications of fungi mycorhize and T. harzianum affected growth of F. Oxysporum f sp. Lycopersici. The incubation period of F. oxysporum on tomato was longer, 20.5 days when applied with mycorrhize 15 g.polybag-1 and T. harzianum 45 g.polybag-1 compared to control 17.75 days. The length of xylem discoloration was only 2.39 cm when treated with FMA 15 g.polybag-1 compared to control 13.44 cm, while xylem discoloration was 6.56 cm when applied with T. harzianum 45 g.polybag-1 compared to control 8.65 cm. Application of mycorrhize 15 g.polybag-1 and T. harzianum 45 g.polybag-1 caused  a decreased percentage of wilting plant. The percentage of wilting plant was 35 % when treated with FMA 15 g.polybag-1 compared to control 74.28% and 42.50% when treated with T. harzianum 45 g.polybag-1 compared to control 54.64%. There was no interaction between fungi mycorrhize and T. harzianum for xylem discoloration and percentage of wilting plant.